Histopathological and Haematological Effects of Mosquito Coil Smoke on Lungs - An Experimental Study on Albino Rats - Syed, Masooma; Balowria, Kamaldeep Singh; Tousia, Sheikh; Jabeen, Nusrat; Faruqi, Nafis Ahmad (Academia Anatomica International, 2019)
Introduction: Mosquito coils are the most preferred anti-mosquito products in many households of Asian countries like India. Short-term exposure to allethrin has been reported to cause toxic effects on respiratory system. Subjects and Methods: Thirty albino rats were divided into five groups (A, B, C, D, and E) of six animals each. Except group A (Control) rest (Group B-E) were exposed to mosquito coil smoke for 4, 6, 8 and 10 weeks respectively. Blood from all the animals was processed to estimate TLC (Total leucocyte count) and results thus attained were analysed using one-way ANOVA test. Rats were sacrificed to procure lung tissue, which was processed by paraffin embedding to obtain haematoxylin and Eosin stained sections. Results: There was significant increase (p value, 0.001) in TLC in all experimental groups compared to control ones. Conclusion: Degenerative changes were obtained in lung tissue of all experimental rats with maximum effect in group Adequate measures should be taken to ensure minimal exposure to coil smoke during domestic use.